Reaction/diffusion at electrode/solution interfaces: the EC2 reaction - LYONS, MICHAEL EDWARD (Electrochemical Science Group, 2009)
A closed form analytical expression is derived for the normalized current versus potential response expected for a rotating disc electrode in which an initial fast electron transfer reaction is followed by a homogeneous electrochemical reaction which exhibits second order kinetics. The effect of the homogeneous reaction on the shape of the voltammetric response curve is calculated.
PUBLISHED
Keywords: Reaction/diffusion equations ; Electrode kinetics ; EC reactions